Kontekstualizm i antyrealizm — próba porównania - Wieczorek, Renata (Filozofia Nauki, 2008)
The study aimed at comparison of two standpoints in the contemporary analitical philosophy: antirealism and contextualism. Three characteristics of the antirealist views will be taken into consideration: